Psychometric evaluation of the Perceived Stress Scale among university students in Northern Brazil - Ferreira, Laiana Soeiro; Silva, Simone Souza da Costa e; Pontes, Fernando Augusto Ramos; Hernandez, José Augusto Evangelho; Silva, Emmanuelle Pantoja; Queiroz, Luana Conceição; Käppler, Christoph de Oliveira; Silva, Jonas Carvalho e (Frontiers in Education, 2026)
Stress is a natural reaction to change or challenge and can lead to various physical, emotional, and behavioral responses. It becomes problematic when stressors persist without relief or relaxation. Academic stress is interpreted as a physiological, emotional, cognitive, and behavioral trigger originating from stimuli and events within the university environment. This study sought evidence of validity and reliability for the 10-item Perceived Stress Scale (PSS-10) based on the scores of 283 university students of both genders from the Northern region of Brazil. The instrument aims to measure the degree to which individuals perceive situations as unpredictable, uncontrollable, and overwhelming. The scale consists of 10 items—six negatively worded and four positively worded. Since its development, the internal structure of the instrument has remained a subject of debate in the literature. In this study, the most frequently tested models in international research were evaluated using Structural Equation Modeling with Confirmatory Factor Analyses. The results showed that the two-factor oblique model (Perceived Stress and Perceived Coping Ability) demonstrated the best fit to the empirical data among the models tested. Nevertheless, the internal consistency value for the Perceived Stress factor fell below the adequate cutoff point. Additionally, the scale scores showed significant positive correlations with the Beck Anxiety Inventory. Overall, despite the limitations of a non-probabilistic, convenience sample, acceptable evidence of internal structure validity, correlation with an external related measure, and reliability was obtained for the scale based on scores from university students in Northern Brazil.